Scarface - Bauer, Steven, 1956-; Bregman, Martin, 1926-; De Palma, Brian; Pacino, Al, 1940-; Pfeiffer, Michelle, 1957-; Stone, Oliver (Universal Studios Home Entertainment, 2006)
En Miami (1980), un inmigrante cubano se hace cargo de un imperio de drogas, mientras que sucumbe a la codicia.